High pressure stent-assisted balloon coronary angioplasty: a case report. - N. Mahanonda (2018)
We reported the first high pressure stent assisted balloon angioplasty successfully implanted in this country. The use of intracoronary stent and its future direction were also reviewed. Regimen for post stent can be adjusted for each individual patient.